Identifying the sources of produced water in the oil field by isotopic techniques - Nguyen , Minh Quy; Hoang , Long; Le , Thi Thu Huong; Luong , Van Huan; Vo , Thi Tuong Hanh (Nuclear Science and Technology, 2014)
The objective of this study is to identify the sources of the formation water in the Southwest Su Tu Den (STD SW) basement reservoir. To achieve the objective, isotopic techniques along with geochemical analysis for chloride, bromide, strontium dissolved in the water were applied. The isotopic techniques used in this study were the determination of water stable isotopes signatures (δ2H and δ18O) and of the 87Sr/86Sr ratio of strontium in rock cutting sample and that dissolved in the formation water. The obtained results showed that the stable isotopes compositions of water in the Lower Miocene was -3‰ and -23‰ for δ18O and δ2H, respectively indicating the primeval nature of seawater in the reservoir. Meanwhile, the isotopic composition of water in the basement was clustered in a range of alternated freshwater with δ18O and δ2H being –(3-4)‰ and -(54-60)‰, respectively). The strontium isotopes ratio for water in the Lower Miocene reservoir was lower compared to that for water in the basement confirming the different natures of the water in the two reservoirs. The obtained results are assured for the techniques applicability, and it is recommended that studies on identification of the flow-path of the formation water in the STD SW basement reservoir should be continued.